2019
DOI: 10.1101/836767
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic risk of cholangiocarcinoma is linked to the autophagy gene ATG7

Abstract: Cholangiocarcinoma is an aggressive cancer originating from the bile duct. Although cholangiocarcinoma does occur in families, to date no specific causative gene has been identified. We identified ATG7 as a cancer susceptibility gene using a joint genetic analysis of an extended pedigree with familial cholangiocarcinoma in combination with a population genetic association study. Affected family members had a germline mutation (c.2000C>T [p.Arg659*]) in the autophagy related gene, ATG7, and all of the affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…In CCA, several pieces of evidence strongly suggest a deregulated autophagy at the initial steps of cholangiocarcinogenesis, where defective autophagy would allow oncogenic transformation. Supporting this theory, Greer et al showed a genetic risk of CCA linked to ATG7 deficiency and therefore autophagy impairment, mediated by a lack of lipidation activity and p62 accumulation compared with wild-type ATG7 carriers [33]. Moreover, precursor BilIN lesions showed higher levels of LC3-II and p62 compared with normal biliary ducts [105], indicative of uncomplete autophagic process, reinforcing the theory of autophagy inhibition as a contributor to carcinogenic transformation.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 91%
See 3 more Smart Citations
“…In CCA, several pieces of evidence strongly suggest a deregulated autophagy at the initial steps of cholangiocarcinogenesis, where defective autophagy would allow oncogenic transformation. Supporting this theory, Greer et al showed a genetic risk of CCA linked to ATG7 deficiency and therefore autophagy impairment, mediated by a lack of lipidation activity and p62 accumulation compared with wild-type ATG7 carriers [33]. Moreover, precursor BilIN lesions showed higher levels of LC3-II and p62 compared with normal biliary ducts [105], indicative of uncomplete autophagic process, reinforcing the theory of autophagy inhibition as a contributor to carcinogenic transformation.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 91%
“…Based on nomograms, they stratified iCCA patients and generated a therapeutic strategy after hepatectomy, demonstrating that nomograms based on autophagy markers can be considered as effective models to predict postoperative survival of iCCA patients [31]. In a very interesting study published in 2019, Atg7 was found to be a causative genetic risk factor for CCA development in a family with a high incidence of pCCA, identifying a germline mutation associated with CCA development [33]. This genetic variant resulted in the accumulation of p62, indicative of impaired autophagy in the tumors of carriers compared with noncarrier tumors, confirming autophagy pathway perturbation as a novel cancer driver mechanism in human tumorigenesis in correlation with the detection of impaired autophagy in BilIN lesions [105].…”
Section: Autophagy Modulation In Cholangiocarcinomamentioning
confidence: 99%
See 2 more Smart Citations
“…In humans, the link between ATG7 dysfunction and cancer formation is only starting to emerge. Recently, familial cholangiocarcinoma (an aggressive cancer of the bile duct) has been associated with ATG7 mutations (preprint: Greer et al , 2019 ). In this study, a number of individuals harbouring inherited monoallelic ATG7 variants (interestingly including the p.Arg659* (NP_ 006386.1) variant identified in Family 1 (Collier et al , 2021 )) were discovered having developed cholangiocarcinoma.…”
Section: Atg7 In Human Diseasementioning
confidence: 99%